Of Walking in Ice : Munich-Paris, 23 November-14 December 1974 - Herzog, Werner, 1942- (Book collections on Project MUSE., 2015)
In the winter of 1974, filmmaker Werner Herzog made a three week solo journey from Munich to Paris on foot. He believed it was the only way his close friend, film historian Lotte Eisner, would survive a horrible sickness that had overtaken her.